Cancer Screening Awareness and Practice in a Middle Income Country; A Systematic Review from Iran - Majidi, Azam; Majidi, Somayye; Salimzadeh, Somayye; Khazaee- Pool, Maryam; Sadjadi, Alireza; Salimzadeh, Hamideh; Delavari, Alireza (Asian Pacific journal of cancer prevention : APJCP, 2017)
Objective: Ageing population and noticeable changes in lifestyle in developing countries like Iran caused an increase in cancer incidence. This requires organized cancer prevention and screening programs in population level, but most importantly community should be aware of these programs and willing to use them. This study explored existing evidence on public awareness and practice, as well as, adherence to cancer screening in Iranian population. Methods: Major English databases including Web of Science, PubMed, Scopus, and domestic Persian databases i.e., SID, Magiran, and Barakat search engines were searched. All publications with focus on Iranian public awareness about cancer prevention, screening, and early detection programs which were published until August 2015, were explored in this systematic review. For this purpose, we used sensitive Persian phrases/key terms and English keywords which were extracted from medical subject headings (MeSH). Taking PRISMA guidelines into considerations eligible documents, were evaluated and abstracted by two separate reviewers. Results: We found 72 articles relevant to this topic. Screening tests were known to, or being utilized by only a limited number of Iranians. Most Iranian women relied on physical examination particularly self-examination, instead of taking mammogram, as the most standard test to find breast tumors. Less than half of the average-risk adult populations were familiar with colorectal cancer risk factors and its screening tests, and only very limited number of studies reported taking at least one time colonoscopy or FOBT, at most 5.0% and 15.0%, respectively. Around half of women were familiar with cervical cancer and Pap-smear test with less than 45% having completed at least one lifetime test. The lack of health insurance coverage was a barrier to participate in screening tests. Furthermore some people would not select to be screened only because they do not know how or where they can receive these services. Conclusion: Low awareness and suboptimal use of screening tests in Iran calls for effective programs to enhance intention and compliance to screening, improving the patient-physician communication, identifying barriers for screening and providing tailored public awareness and screening programs.